1998
DOI: 10.1029/98ja02245
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of the lower hybrid wave cavities detected by the FREJA satellite

Abstract: Abstract. Localized electrostatic wave packets in the frequency region of lower hybrid waves have been detected by the instruments on the FREJA satellite and also earlier by instrumented rocket payloads. These waves are often associated with local density depletions, indicating that the structures can be interpreted as wave-filled cavities which are strongly elongated along the magnetic field. The basic features of the observations are discussed, providing a survey of the conditions for occurrence and spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
(8 reference statements)
3
38
0
Order By: Relevance
“…A recent analysis of Freja data [Kjus et al, 1998] discusses the basic statistical characteristics of lower hybrid waves and associated density depletions. In the observational part of their paper, Kjus In conclusion, we have shown that when lower hybrid wave radiation impinges on a density striation in a controlled experiment, the interaction produces large field amplitudes in the gradient regions.…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…A recent analysis of Freja data [Kjus et al, 1998] discusses the basic statistical characteristics of lower hybrid waves and associated density depletions. In the observational part of their paper, Kjus In conclusion, we have shown that when lower hybrid wave radiation impinges on a density striation in a controlled experiment, the interaction produces large field amplitudes in the gradient regions.…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…These are values in an inertial frame of reference. On Cluster, the plasma drift speed generally dominates over the spacecraft speed in this frame, so that the number of LHCs encountered in the plasma reference frame The occurrence frequency for some of the Freja orbits has been determined by Kjus et al (1998) to be about 2 per kilometer perpendicular to the magnetic field. The LHCs thus were a factor 2000 more common per kilometer in the Freja data compared to Cluster.…”
Section: Discussion Of Occurrence Statisticsmentioning
confidence: 99%
“…It is of interest to see where the LHCs are found in the Viking and Cluster data, so that we can compare with occurrence investigations from the Freja satellite Kjus et al, 1998). We also compare how common the LHCs are in the inner magnetosphere with those observations from the upper ionosphere.…”
Section: Location Of the Lhcsmentioning
confidence: 99%
“…The sounding rockets, which move slowly and have high telemetry bandwidth, have provided great detail for just a few events (e.g. Pinçon et al, 1997), while Freja, in its nearly three years of operation, yielded a wealth of observations providing occurrence statistics Kjus et al, 1998). It is of great interest to supplement the Freja results from 1500-1750 km altitudes with statistics from the Astrid-2 altitude of 1000 km.…”
Section: Scientific Objectivesmentioning
confidence: 99%